2011
DOI: 10.1007/s11357-010-9203-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Purkinje cell death is steroid dependent: RORα haplo-insufficiency impairs plasma and cerebellar steroids and Purkinje cell survival

Abstract: A major problem of ageing is progressive impairment of neuronal function and ultimately cell death. Since sex steroids are neuroprotective, their decrease with age may underlie age-related neuronal degeneration. To test this, we examined Purkinje cell numbers, plasma sex steroids and cerebellar neurosteroid concentrations during normal ageing (wild-type mice, WT), in our model of precocious ageing (Rora+/sg, heterozygous staggerer mice in which expression of the neuroprotective factor RORα is disrupted) and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 83 publications
(123 reference statements)
1
11
0
Order By: Relevance
“…In addition to our finding that RORA regulates the transcription of genes involved in the enzymatic conversion of male to female hormones, neurohistological studies by other groups have reported that loss of Purkinje neurons in male Rora-deficient staggerer mice occurs much earlier in life in comparison to female staggerer mice [ 42 , 43 ], revealing a sexually dimorphic response to Rora deficiency. We recently demonstrated that male and female sex hormones inversely regulate RORA expression in human neuronal cells by suppressing and enhancing RORA expression, respectively [ 16 ].…”
Section: Introductionsupporting
confidence: 59%
“…In addition to our finding that RORA regulates the transcription of genes involved in the enzymatic conversion of male to female hormones, neurohistological studies by other groups have reported that loss of Purkinje neurons in male Rora-deficient staggerer mice occurs much earlier in life in comparison to female staggerer mice [ 42 , 43 ], revealing a sexually dimorphic response to Rora deficiency. We recently demonstrated that male and female sex hormones inversely regulate RORA expression in human neuronal cells by suppressing and enhancing RORA expression, respectively [ 16 ].…”
Section: Introductionsupporting
confidence: 59%
“…In our transplants, the number of mouse PCs did not decrease in older rats, further suggesting that lifespan of the transplanted neurons was not dictated by their mouse genetic background, but by the rat microenvironment. In mice, agedependent loss of PCs has been related to a decrease in concentration of circulating sex steroid hormones (27). However, the increased survival of mouse PCs after xenotransplantation is unlikely to depend on differences in sex steroid, as levels and oscillations of those hormones are similar in aging mice and rats (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…PCs are representative models for investigating dendrite development, as well as the function of circulating sex steroids and neurosteroids in neuronal death. Neuronal loss in Rorα +/sg leads to a decline in circulating sex steroids and cerebellar neurosteroids, thus inducing PC death during normal aging 51 . Embryonic knockdown using a miRNA against RORα results in PC mislocation and primitive dendrites.…”
Section: Control Of Cerebellar Development and Circadian Rhythms By Rorαmentioning
confidence: 99%